The trilobite biostratigraphy for the Balang and "Tsinghsutung" formations, Cambrian Series 2, Stage 4 in the Balang area, Jianhe, Guizhou, South China - Zhao, Y.; Peng, S.; Yuan, J.; Esteve, J.; Yang, X.; Wu, M.; Chen, Z. (Estudios Geológicos, 2019)
Ongoing work is carrying out in the Balang and "Tsinghsutung" formations to aim a suitable candidate for the base of the Cambrian Series 2, Stage 4. The revision of the trilobite systematics and zonation shed light about the stratigraphic distribution and the geographical distribution of the new trilobite-based zones in the Balang area (South China). Our results suggest that either Otyctocarella duyunensis or Arthricocephalus chauveaui could be good candidates since they also occur in the Eoaagnostus roddyi-Arthricocephalus chauveaui Zone of the Henson Gletscher Formation, North Greenland.